PENGARUH SERVICE QUALITY DAN FLEKSIBELITAS E-PAYMENT TERHADAP KEPUASAN PELANGGAN WIFI BUMDESA DI DESA BANJARWUNGU, KABUPATEN SIDOARJO - Lestari, Meylani Dwi; Pratiwi, Ni Made Ida; Pudjianto, Agung (Research Journal of Social Science and Economics, 2025)
Changes from time to time always progress, both advances in culture, social, economic and technology. Technological progress is one of the conveniences created by humans which plays a very important role in buying and selling activities, changing the system where the system that was originally used, namely conventional, has turned into digital. The purpose of this study is to determine and analyze the effect of Service Quality, E-Payment and Customer Satisfaction variables. This study uses a quantitative method probability approach of the Simple Random Sampling type. The number of samples in the study were 95 respondents. The data collection technique used by researchers is a closed e-questionnaire type. Based on the results of research conducted by researchers related to Service Quality and E-Payment Flexibility on BUMDesa WIFI Customer Satisfaction in Banjarwungu Village, Sidoarjo Regency, it can be concluded that partially, the Service Quality variable has an influence on Customer Satisfaction and the E-Payment variable has an influence on Customer Satisfaction. Simutaneously, Service Quality and E-Payment variables have an influence on Customer Satisfaction.